BRAFV600E-mutation is invariably present and associated to oncogene-induced senescence in Erdheim-Chester disease. Issue 8 (26th March 2014) - Cangi, Maria Giulia; Biavasco, Riccardo; Cavalli, Giulio; Grassini, Greta; Dal-Cin, Elena; Campochiaro, Corrado; Guglielmi, Barbara; Berti, Alvise; Lampasona, Vito; von Deimling, Andreas; Sabbadini, Maria Grazia; Ferrarini, Marina; et al.
Abstract : Objectives: Erdheim-Chester disease (ECD) is a rare form of histiocytosis characterised by uncontrolled chronic inflammation. The oncogenic BRAF V600E mutation has been reported in biopsies in 19 out of 37 patients with ECD from the largest published cohort, but never found in the patients' peripheral blood. Also, the role of the mutation in the pathogenesis of the disease has not been elucidated yet. BRAF V600E has been associated with oncogene-induced senescence (OIS), a protective mechanism against oncogenic events, characterised by the induction of proinflammatory pathways. Methods: We verified the BRAF status in biopsies and peripheral blood from 18 patients with ECD from our cohort and matched controls by means of immunohistochemistry and of an ultrasensitive assay, based on the combination of a locked nucleic acid PCR and pyrosequencing. Droplet digital PCR was used to confirm the findings. We also evaluated the presence of senescence markers in ECD histiocytes. Results: BRAF V600E mutation was present in all the biopsy and peripheral blood samples from patients with ECD and in none of the controls. ECD histiocytes and a fraction of circulating monocytes from patients with ECD showed signs of a constitutive activation of the MAPK pathway. Moreover, BRAF-mutated histiocytes expressed markers of OIS. Conclusions: The oncogenic BRAF V600E mutation is present in biopsies and in the peripheral blood from all patients with ECD who were evaluated and is associated with OIS. These findings have significant implications for the pathogenesis, diagnosis and treatment of ECD.